Natural convective heat transfer from narrow plates - Oosthuizen, Patrick H. (Springer, 2013)
Natural Convective Heat Transfer from Narrow Plates deals with a heat transfer situation that is of significant practical importance but which is not adequately dealt with in any existing textbooks or in any widely available review papers. The aim of the book is to introduce the reader to recent studies of natural convection from narrow plates including the effects of plate edge conditions, plate inclination, thermal conditions at the plate surface and interaction of the flows over adjacent plates. Both numerical and experimental studies are discussed and correlation equations based on the results of these studies are reviewed
Introduction -- Natural Convective Heat Transfer from Narrow Vertical Plates -- Natural Convective Heat Transfer from Inclined Narrow Plates -- Effect of Edge Conditions on Natural Convective Heat Transfer from Narrow Vertical Plates -- Experimental Results for Natural Convective Heat Transfer from Vertical and inclined narrow Plates -- Turbulent Natural Convective Heat Transfer from Narrow Plates -- Natural Convective Heat Transfer from two Adjacent Narrow Plates
Keywords: Ingenieurwissenschaften; Engineering; Surfaces (Physics)